ANALISIS PENENTUAN KOMODITI UNGGULAN PADI SAWAH PADA SETIAP KECAMATAN DI KABUPATEN MOROWALI - Wijaya, Putu Bagus; Laapo, Alimudin; Kalaba, Yulianti (AGROTEKBIS, 2017)
This study aims to analyze the best places for rice commodities in sub-districts of Morowali Regency based on its production. This research was conducted by using secondary data for 2 months starting from January 20, 2017 until March 20, 2017 in Morowali Regency. The respondents in this study were determined intentionally (Purposive). Data were analyzed by using Location Quotien (LQ) analysis. The result shown that average LQ value in morowali district from 2011 until 2015 is 0,85157. Result from LQ analysis of sub-districts showed there were three regions superior in field of rice commodity in 2015. That is West Bungku Sub District Â 1.08124, Bumi Raya Sub District 1,18688, and Wita Ponda Sub District 1,212402.Â Keywords: Base Production, and Nonbase, Paddy Rice